How do i do this

Thank you for the opportunity to help you with your question!

A = p+prt

A - p = prt

(A- p) / pt = r

r = (A- p) / pt

answer is

r = (A- p) / pt ............................answer

r = (A /pt ) - (1/t),,,,,,,,,,,,,,,,,,,,,,,,,,,,,,answer

both answers are same . ...you can select from your choices

subtract p from both sides,then

A-p = p+prt

now divide by pt on both sides

(A- p) / pt = prt / pt

so answer is

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up